Identifikasi Cacing Trematoda dan Gambaran Patologi Ginjal Burung Merpati yang Terinfeksi (IDENTIFICATION AND PATHOLOGICAL FEATURES OF TREMATODE IN PIGEON’S KIDNEY) - Sahara, Ana; Prastowo, Joko; PriyoWidodo, Dwi; Rohayati, Eryl Sri; Widyarini, Sitarina (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
This study is conducted to identify species of trematode and its pathological features in pigeons’kidney. Twenty five of Yogyakarta pigeons were examined for trematode infection in kidneys. One ofkidneys was mashed in mortar with a little water, the other was examined for histopathological featuresstained with hematoxyline-eosin.Trematodes found were stained with Schmison ´s Carmine. Seven pigeons(28%) were infected by trematode with non significant clinical features. Identification trematodescharacterized by oral sucker, pharynx, testes are slighty diagonal in position, irregular in shape and intracaecal. Ovary pretesticular and vitellaria widespread from anterior ovarium to the posterior body.Histopathological examination showed segment of trematode in the medullary collecting ducts lumen,dilatation, flattening and emptyness of ducts epithelial cells, emptyness, giant cells and dominationmononuclear cell in interstitial tissue, characterizing a granulomatous nephritis. Trematodes foundidentified as Paratanaisia bragai. The trematodes were found in very dilated medullary collecting ductsand caused inflammation in adjacent tissues. Further studies are needed to find out vector of trematodein pigeons .
Keywords: Dove, kidney, trematode, Paratanaisia bragai